Low-temperature thermal expansion of pure and inert gas-doped fullerite C60 - Aleksandrovskii, A.N.; Sundqvist, B.; Moricca, S.; Manzhelii, V.G.; Gavrilko, V.G.; Gadd, G.E.; Esel`son, V.B.; Dolbin, A.V.; Bakai, A.S.; Udovidchenko, B.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The low temperature (2-24 K) thermal expansion of pure (single-crystal and polycrystalline) C60 and polycrystalline C60 intercalated with He, Ne, Ar, and Kr has been investigated using the high-resolution capacitance dilatometer. The investigation of the time dependence of the sample length variations DL(t) on heating by DT shows that the thermal expansion is determined by the sum of positive and negative contributions, which have different relaxation times. The negative thermal expansion usually prevails at helium temperatures. The positive expansion is connected with the phonon thermalization of the system. The negative expansion is caused by reorientation of the C60 molecules. It is assumed that the reorientation is of a quantum character. The inert gas impurities affect the reorientation of the C60 molecules very strongly, especially at liquid helium temperatures. A temperature hysteresis of the thermal expansion coefficient of Kr- and He-C60 solutions has been revealed. The hysteresis is attributed to orientational polyamorphous transformation in these systems.